Assessing peer effects and subsidy impacts in conservation technology adoption: Application to grazing management choices. Issue 3 (29th August 2022) - Che, Yuyuan; Feng, Hongli; Hennessy, David A.
Abstract: Rotational grazing has the potential to provide environmental and economic benefits; however, the adoption rate is about 30% in the United States. We develop a model to examine peer networking and grazing practice decisions, and how subsidies affect decisions in the presence of peer effects. We apply a simultaneous‐equations model to address endogeneity issues with peer effects that are measured as either the number of adopters a rancher knows or the extent of adoption in a rancher's neighborhood. Empirical analysis provides evidence of significant peer effects on rotational grazing adoption. Incentive policies have multiplier effects on adoption through peer networking.